Identification of inappropriate medication use in elderly patients with frequent emergency department visits. (July 2014) - Wong, Jeffrey; Marr, Patricia; Kwan, Debbie; Meiyappan, Soumia; Adcock, Lesley
Objective: To determine the demographic and health care characteristics of elderly family health team patients who are frequent emergency department (ED) users, focusing on potentially inappropriate medications (PIMs) and access to primary care services. Design: Cross-sectional retrospective chart review. Setting: Academic family medicine clinic in Toronto, Ontario. Participants: A total of 46 elderly patients (age >65 years) with 4 or more visits to a University Health Network–affiliated ED between April 1, 2010, and March 31, 2011. Main outcome measures: Using the validated STOPP (Screening Tool of Older Persons' potentially inappropriate Prescriptions) criteria, PIMs were identified. The primary objective was to determine whether PIMs were associated with more frequent ED use. The secondary objective was to determine whether patients who had previously undergone a clinic pharmacist-led medication review had fewer PIMs. We also determined the health characteristics of these patients at the time of their last ED visit of the study period. Utilization of primary care resources, both prior to and after ED visits, was determined. Results: Sixty-five percent of patients were taking at least 1 PIM. The total number of PIMs in the study population was 71. Having more PIMs was significantly correlated with a higher number of ED visits ( r = 0.32, p < 0.05). Patients with a previous medication review had a similar number of PIMs compared with those without a review. The mean number of concurrent medications was 12.1 and the mean Charlson Comorbidity Index score was 3.7. Significant delay between hospital discharge and primary care follow-up (median 13 days) was observed. Conclusion: Elderly patients who are more frequent ED users have a greater number of PIMs. Primary care resources appear to be underused in this population.